High triglycerides to HDL-cholesterol ratio is associated with insulin resistance in normal-weight healthy adults - Pantoja-Torres, Betzi (2018)
Aim: To evaluate the association between high triglyceride/HDL-cholesterol (TG/HDL-C) ratio and insulin resistance (IR) or hyperinsulinemia after oral glucose tolerance test (OGTT) in normal-weight healthy adults. Methods: We carried out an analytical cross-sectional study in euthyroid non-diabetic adults, who attended the outpatient service of a private clinic in Lima-Peru from 2012 to 2016. Participants were divided in two groups according to the presence or absence of high TG/HDL-C ratio, IR or hyperinsulinemia after OGTT. TG/HDL-C ratio values ≥ 3 were considered as high. IR was defined as a Homeostasis Model Assessment (HOMA-IR) value ≥ 2.28 and hyperinsulinemia after OGTT as a serum insulin value ≥ 80μU/mL after 120 min of 75-g glucose intake. We elaborated crude and adjusted Poisson generalized linear models to evaluate the association between high TG/HDL-C ratio and IR or hyperinsulinemia after OGTT and reported the prevalence ratio (PR) with their respective 95% confidence intervals (95%CI). Results: We analyzed the data of 118 individuals. Prevalence of high TG/HDL-C ratio was 17.8% (n = 21) while the prevalence of IR and hyperinsulinemia after OGTT was 24.6% (n = 29) and 17.0% (n = 20), respectively. TG/HDL-C-ratio values were positively correlated with HOMA-IR (r = 0.498; p < 0.01) and serum insulin after OGTT (r = 0.326; p < 0.001). In the adjusted model, high TG/HDL-C ratio was associated with both IR (aPR = 3.16; 95%CI: 1.80–5.77) and hyperinsulinemia after OGTT (aPR = 2.36; 95%CI: 1.20–4.63). Conclusions: High TG/HDL-C ratio was associated with both IR markers used in our study, appearing to be a clinically useful tool to assess IR in euthyroid normal-weight adults without type 2 diabetes mellitus. © 2018 Diabetes India